2016
DOI: 10.3171/2015.4.spine14847
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of low lumbar osteoporotic vertebral collapse: a single-institution experience

Abstract: OBJECT Low lumbar osteoporotic vertebral collapse (OVC) has not been well documented compared with OVC of the thoracolumbar spine. The differences between low lumbar and thoracolumbar lesions should be studied to provide better treatment. The aim of this study was to clarify the clinical and imaging features as well as outcomes of low lumbar OVC and to discuss the appropriate surgical treatment. METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 29 publications
2
63
0
Order By: Relevance
“…Research on spinopelvic parameters has advanced, and it is now possible to evaluate the ideal lumbar lordosis. Meanwhile, according to Nakajima et al, mismatch of parameters did not necessarily increase the rate of complications postoperatively with surgeries involving the ML lesion 10) . In addition, cases exist in which obtaining full-length radiography of the spinal column prior to surgery proved impracticable and avoiding highly invasive surgical procedures is deemed necessary.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Research on spinopelvic parameters has advanced, and it is now possible to evaluate the ideal lumbar lordosis. Meanwhile, according to Nakajima et al, mismatch of parameters did not necessarily increase the rate of complications postoperatively with surgeries involving the ML lesion 10) . In addition, cases exist in which obtaining full-length radiography of the spinal column prior to surgery proved impracticable and avoiding highly invasive surgical procedures is deemed necessary.…”
Section: Discussionmentioning
confidence: 95%
“…Yeoh et al reported observing fewer complications as a result of percutaneous spinal fusion surgery in the course of treatment to address vertebral fractures associated with ankylosing spondylitis 19) . In addition, Nakajima et al described the importance of osteoporosis treatment as an approach to prevent implant-related postoperative complications arising after OVF surgery 10) . Among our cases, 54% had perioperative complications and 23% had instances of revision surgery that are considered to be frequent; the causes are presumed to be the presence of comorbidities and osteoporosis, age of around 80 years, and the impact of invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multicenter cohort of 403 patients in Japan who underwent fusion surgery for OVC with neurological de cits, a thoracolumbar junction lesion at T12 and L1 was most frequent, but 18.9% of cases had low lumbar OVC below L3 [1]. Clinical and imaging features in low lumbar OVC may differ from those in thoracolumbar OVC, based on our previous ndings [2].…”
Section: Introductionmentioning
confidence: 85%
“…Each OVC was classi ed as one of four types based on its appearance on a lateral projection in a neutral position (Fig. 1) [2]: type 1 is a wedge-type collapse de ned as a ratio of the anterior to posterior height of the vertebral body of <60%; type 2 is a at or vertebra plana-like fracture with uniform compression; type 3 is a concave or H-shaped fracture with anterior spur formation or sclerotic change; and type 4 is a burst fracture with severe destruction of the anterior vertebral body. Type 2 collapse often appears as intervertebral cleft formation on radiographs or MRI.…”
Section: Outcomes and Radiological Measurementsmentioning
confidence: 99%